2012
DOI: 10.1074/jbc.m112.372318
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific Protease 9x Deubiquitinates and Stabilizes the Spinal Muscular Atrophy Protein-Survival Motor Neuron

Abstract: Background: Spinal muscular atrophy (SMA) is a devastating genetic disorder caused by low levels of survival motor neuron (SMN) protein.Results: Ubiquitin-specific protease 9x (Usp9x) interacts with, deubiquitinates, and stabilizes SMN. Conclusion: Usp9x likely deubiquitinates SMN to protect it from Ub-dependent degradation. Significance: Usp9x is a key mediator that regulates the protein levels of SMN and the SMN complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 77 publications
(82 reference statements)
4
52
0
1
Order By: Relevance
“…DUB inhibitors can also be used to augment protein ubiquitylation and increase substrate detection; however, proteasome impairment was found to be a more effective approach for increasing levels of ubiquitylation sites (29,30 pharmacological DUB inhibition results in the widespread accumulation of substrates, similar to proteasome inhibition, which is contrary to what might be predicted upon DUB inhibition. This is because many studies have reported a decrease in substrate abundance upon RNAi-based knockdown of individual DUBs (33)(34)(35)(36)(37). This discrepancy may be explained by the fact that although knockdown results in protein depletion, an inhibitor inactivates the enzyme, possibly allowing for sustained substrate binding and possible sequestration.…”
mentioning
confidence: 72%
“…DUB inhibitors can also be used to augment protein ubiquitylation and increase substrate detection; however, proteasome impairment was found to be a more effective approach for increasing levels of ubiquitylation sites (29,30 pharmacological DUB inhibition results in the widespread accumulation of substrates, similar to proteasome inhibition, which is contrary to what might be predicted upon DUB inhibition. This is because many studies have reported a decrease in substrate abundance upon RNAi-based knockdown of individual DUBs (33)(34)(35)(36)(37). This discrepancy may be explained by the fact that although knockdown results in protein depletion, an inhibitor inactivates the enzyme, possibly allowing for sustained substrate binding and possible sequestration.…”
mentioning
confidence: 72%
“…Previously, USP9X was found to interact with another Tudor domain-containing protein, survival motor neuron (SMN) protein [50, 51]. Mutation/deletion of SMN-coding gene, SMN1 , accounts for 95% of spinal muscular atrophy (SMA), an autosomal recessive disorder that results in degeneration of α-motor neurons in the spinal cord [52].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the E3 ubiquitin-protein ligase mind bomb-1 (Mib1) ubiquitinates SMN, targeting it for degradation (20). In addition Usp9x (also known (21). Usp9x/FAM also interacts with Mib1 (22), suggesting that they act together to regulate SMN protein levels.…”
Section: Ml372 Is Brain Penetrant and Has A Reasonable Exposure And Hmentioning
confidence: 99%